ANALISIS HUBUNGAN TINGKAT KECEMASAN DAN NYERI PERSALINAN KALA 1 PRIMIPARA DI WILAYAH KERJA PUSKESMAS KOTA PEKALONGAN - Rahmawati, Agustina; Hartati, Hartati; Sumarni, Sumarni (BAPPEDA Kota Pekalongan, 2016)
ANXIETY IS A NATURAL DISRUPTION OF FEELING SIGNED BY DEEP ANXIETY OR NERVOUS /WORRIES AND THE BEHAVIOUR COULD BE DISRUPTED BUT STILL IN NORMAL LEVEL. BESIDES BIRTHING PAIN IS A MECHANISMOF BODY PROTECT APPEAR IF THERE IS A TORN BODY TISSUE AND IT WILL CAUSE THE REACTION BY MOVING PAIN STIMULA. BASED ON THE INTRODUCTION OF STUDY DONE BY PUSKESMAS BENDAN, PUSKESMAS JENGGOT, PUSKESMAS KUSUMA BANGSA FROM 10 MOTHERS GIVES BIRTH STEP 1 PRIMIPARA, GOT RESULT THAT 8 RESPONDENTS (80)GET HARD ANXIETY, AND 2 RESPONDENTS (20%) HAVE MEDIUM LEVEL OF PAIN, THE MAIN GOAL OF THIS STUDY IS TO KNOW THE RELATION BETWEEN ANXIETY LEVEL OF BIRTHING PAIN STEP 1 PRIMIPARA. THE WRITER USED CORRELATIONAL DESCRIPTIVE ANALISIS METHOD, SAMPLING TECHNIQUE IN THIS STUDY USED CROSS SECTIONAL. THE NUMBER OF POPULATION IS ABOUT 84 RESPONDENTSOF MOTHERS PRIMIPARA AND THE AMOUNT OF SAMPLE IS ABOUT 68 RESPONDENTS OF BIRTHING MOTHERS PRIMIPARA. BASED ON THE RESULT OF STUDY DONE TO RESPONDENTS IN THE WORK AREA OF PUSKESMAS IN PEKALONGAN CITY THAT RESPONDENTS HAVING WORRIES IN MEDIUM LEVEL. THAT IS ABOUT 43 RESPONDENTS (63,3%). HARD WORRIES ABOUT 20 RESPONDENTS (39,4) AND LIGHT WORRIES ABOUT 8 RESPONDENTS (7,4%) . BESIDES RESPONDENTS HAVING MEDIUM PAIN IT IS ABOUT 19 RESPONDENTS (27,9%) , LIGHT PAIN ABOUT 6 RESPONDENTS (8,87%). BASED ON THE RESULT , IT WOULD BE BETTER IF THE MEDICAL ASSISTANCES ESPECIALLY MIDWIFE CAN GIVE KNOWLEDGE OR COMPLETE INFORMATION ABOUT BIRTHING PROCESS CAN GIVE KNOWLEDGE OR COMPLETE INFORMATION ABOUT BIRTHING PROCESS SO CAN DECREASE WORRIES LEVEL TO INPARTU PATIENTS STEP 1 PRIMIPARA.